2014
DOI: 10.1371/journal.pone.0085267
|View full text |Cite
|
Sign up to set email alerts
|

Identification of an HLA-A2-Restricted Epitope Peptide Derived from Hypoxia-Inducible Protein 2 (HIG2)

Abstract: We herein report the identification of an HLA-A2 supertype-restricted epitope peptide derived from hypoxia-inducible protein 2 (HIG2), which is known to be a diagnostic marker and a potential therapeutic target for renal cell carcinoma. Among several candidate peptides predicted by the HLA-binding prediction algorithm, HIG2-9-4 peptide (VLNLYLLGV) was able to effectively induce peptide-specific cytotoxic T lymphocytes (CTLs). The established HIG2-9-4 peptide-specific CTL clone produced interferon-γ (IFN-γ) in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 11 publications
(16 citation statements)
references
References 43 publications
0
16
0
Order By: Relevance
“…These results strongly indicated that vaccination with oncoantigen‐derived peptides can induce specific CTL potently cytotoxic to HLA‐A matched cancer cells expressing oncoantigen. Thus, we identified several oncoantigen‐derived epitope peptides by measuring the induction of activation of specific CTL . We have also tested these peptides in clinical investigations against several urological cancers.…”
Section: Development Of Peptide Vaccine Therapy Using Oncoantigenmentioning
confidence: 99%
“…These results strongly indicated that vaccination with oncoantigen‐derived peptides can induce specific CTL potently cytotoxic to HLA‐A matched cancer cells expressing oncoantigen. Thus, we identified several oncoantigen‐derived epitope peptides by measuring the induction of activation of specific CTL . We have also tested these peptides in clinical investigations against several urological cancers.…”
Section: Development Of Peptide Vaccine Therapy Using Oncoantigenmentioning
confidence: 99%
“…As one of the approaches to develop a novel treatment option, we previously developed the HLA-A*0201/0206-restricted HIG2-derived epitope peptide, HIG2-9-4 [8]. In the present study, we conducted a phase I clinical trial using the HIG2-9-4 peptide for patients with advanced RCC.…”
Section: Discussionmentioning
confidence: 99%
“…HIG2-derived 9- and 10-mer peptides that have high binding affinity to HLA-A:*02:01 were identified as candidates by using the binding prediction software, BioInformatics and molecular analysis section (BIMAS), and the homologous sequences were screened by using the homology search program, basic local alignment search tool (BLAST), as previously reported [8]. The selected high-affinity peptide, HIG2-9-4 peptide (VLNLYLLGV), was manufactured as good manufacturing practice (GMP) grade at a purity of >95 % for the clinical trial by the American Peptide Company Inc. (Sunnyvale, CA).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, theoretically, integrated application of six servers will improve the accuracy of in silico identification of CTL epitopes in Rv3117 and Rv3120 proteins. In fact, these online servers have been successfully used for the identification of T cell epitopes against different pathogens [24,25] and cancers [26]. Since NetCTL provides epitope prediction with 54-89% sensitivity and 94-99% specificity, we first employed NetCTL to predict CTL epitopes in Rv3117 and Rv3120 proteins at the default prediction value 0.75, which had 80% sensitivity and 97% specificity in a previous study [12].…”
Section: Proteinmentioning
confidence: 99%